Pola Komunikasi Interpersonal Asatidz dalam Menumbuhkan Nilai-Nilai Kepemimpinan Santri di MTS Persis 38 Padalarang - Ghina Amalia Fadiya; Nia Kurnia (Bandung Conference Series: Islamic Broadcast Communication, 2023)
Abstract. The purpose of this study is to find out the method of teachers in developing student leadership values, to know about the communication method of teachers in developing student leadership values, to identify the interpersonal communication obstruction of teachers in developing student leadership values, and to know about interpersonal communication pattern of teachers in developing student leadership values. The type of the reaserch is qualitative by using descriptive method. The technique of collecting data is conducted by writing the result of observation and the result of interview which is supported by documentation data and literature. The result of the study shows that the method used by teachers in developing student leadership values is using persuasive method of communication through habituation of kultum, ihtifal usbu’i, congregetional prayer, LDKS (Student Leadership Basic Training) and Mabit (The night of buiding up faith and piety). The communication method that used is habituation and personal approach. Then the obstruction is on the outside of the school environment. Meanwhile the interpersonal communication pattern by using circular communication. Abstrak. Penelitian ini bertujuan untuk mengetahui metode para asatidz dalam menumbuhkan nilai-nilai kepemimpinan santri, mengetahui saluran komunikasi para asatidz dalam menumbuhkan nilai-nilai kepemimpinan santri, mengetahui hambatan komunikasi interpersonal asatidz dalam menumbuhkan nilai-nilai kepemimpinan santri , dan untuk mengetahui pola komunikasi interpersonal para asatidz dalam menumbuhkan nilai-nilai kepemimpinan santri. Jenis penelitian ini adalah kualitatif dengan metode deskriptif. Dengan teknik pengumpulan data mencatat dari hasil pengamatan dan hasil wawancara yang didukung dengan data dokumentasi dan kepustakaan. Hasil penelitian menunjukkan bahwa metode para asatidz dalam menumbuhkan nilai-nilai kepemimpinan menggunakan metode komunikasi persuasif dengan pembiasaan kultum, ihtifal usbu’I, sholat berjama’ah, LDKS (Latihan Dasar Kepemimpinan Santri) dan Mabit (Malam Bina Iman dan Takwa). Saluran yang digunakan yaitu pembiasaan serta pendekatan personal. Hambatannya adalah dari luar lingkungan sekolah. Adapun pola komunikasi interpersonalnya dengan komunikasi sirkular.